Creative Black Comedy Short Film “THE SICK AND THE WEIRD” - Jampakhaow, Thanawat; Julakarn, Sutee; Wattananon, Wichit (Journal of Fine and Applied Arts Khon Kaen University, 2025)
Spiritual security is one of the sets of stability of life, the main spiritual security anchoring the mind of a person who is on the verge of death. Most of the time, the mind is distracted, frightened, unconscious. Today, there are still people who lack psychological stability who are used as a tool to exploit certain groups of people based on their beliefs and faith. As a result, the researcher has taken these events and narrated them through dark comedy films that satirize the dark side of humans and death in a humorous manner to diminish the severity of the story. The research objectives are: 1) to study the concept of self-deception, analyze the behavior and phenomena of belief in cult groups, 2) to study the form of dark comedy films, and 3) to create dark comedy short films based on the concept of self-deception. By the scope of research on the issue of self-deception concepts. The presentation of dark comedy films and the creation of short films from the scope of content study of self-deception behavior and the phenomenon of belief in strange cults. The results of the research can be summarized as follows: Phase 1 found that self-deception is a state of spiritual security, which is basic security, that is, psychological security is one of the sets of stability of life. Faith or faith provides a certain level of mental stability. Phase 2 sees the black comedy film format as a comedy film that picks up on issues in society and presents them in order to reduce the seriousness, especially the issue of death. and Phase 3: Design and create the film "Strangers Break the Cult of Fanaticism" The idea of presenting the film is a satire on the murder of dissidents through a mystical cult belief in a black comedy designed to show the absurdity of the world. Society, people, and design the creation to have a rawness that will convey a story covered in death.